Rekonseptualisasi Manajemen Perencanaan Program Legislasi Nasional Guna Mewujudkan Pembangunan Hukum Berkelanjutan - Ihsanul Maarif (CV Rewang Rencang, 2024)
The development of national law is part of the national development system aimed at realizing the goals of the state. The guidelines and foundations for legal development in Indonesia are contained in the National Legislation Program (Prolegnas), the medium-term Prolegnas is carried out for a period of 5 years. Legal development in Indonesia seems slow, this is possible because of the current concept of Prolegnas. The results of the study stated that the Prolegnas should be conceptualized to be prepared every 1 year, this is so that there is a good evaluation, the community can participate in the formation of the Law, in accordance with the annual principle in state finance, and the Law made by the House of Representatives can follow the development of the times and people's lives.